Tax avoidance among FBM KLCI Firms: Prevalence and sectoral trends - Zeroual, Sif Eddine; Yamami, Sara (The International tax journal, 2025)
This study investigates the prevalence and sectoral differences of corporate tax avoidance among firms listed on the FBM KLCI from 2018 to 2022. Using the Cash Effective Tax Rate (Cash-ETR) as the primary measure, secondary data were collected from annual financial reports and analyzed through descriptive statistics and sectoral comparisons. The findings reveal that tax avoidance is pervasive, with average Cash-ETRs ranging from 16.8% to 17.9%, significantly lower than Malaysia’s statutory tax rate of 24%. Sectoral analysis highlights higher levels of tax avoidance in the media, real estate, technology, and agriculture sectors, attributed to financial incentives and sector-specific policies. Despite regulatory efforts introduced in 2018 to reduce tax avoidance, firms continued to exploit available mechanisms, particularly during the COVID-19 pandemic. This study provides important empirical evidence on tax avoidance behaviors among Malaysia’s top firms by market capitalization and offers practical insights for policymakers seeking to strengthen corporate tax compliance frameworks.